The Effect of MSME Final Income Tax Rate Changes and PSA Merdeka 78 Incentives on Tax Revenue: The Mediating Role of Taxpayer Compliance - Syamsul Aspar Basri; Faizul Mubarok; Ahmad Syarief Iskandar (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the effects of changes in the Final Income Tax rate for individual Micro, Small, and Medium Enterprises (MSMEs) and the PSA Merdeka 78 administrative penalty reduction incentive on tax revenue, with taxpayer compliance as a mediating variable at the South Makassar Primary Tax Office. A causal quantitative design was applied to 72 monthly time-series observations covering six years. The data were analyzed using descriptive statistics, classical assumption tests, path-analysis regressions, and the Sobel test in SPSS. Changes in the MSME final income tax rate positively affected taxpayer compliance (β=0.264; p=0.019) and tax revenue (β=0.372; p<0.001). PSA Merdeka 78 also positively affected taxpayer compliance (β=0.291; p=0.010) and tax revenue (β=0.869; p<0.001). Taxpayer compliance did not significantly affect tax revenue (β=0.026; p=0.063) and did not mediate either fiscal-policy relationship. The findings indicate that revenue improvements were driven mainly by the direct effects of rate adjustment and penalty relief rather than by changes in compliance.